2021
DOI: 10.1111/jcpt.13567
|View full text |Cite
|
Sign up to set email alerts
|

Progestin‐primed ovarian stimulation protocol with or without letrozole for patients with normal ovarian reserve: a retrospective cohort study

Abstract: What is known and Objective:To compare the characteristics and efficacy of progestin-primed ovarian stimulation (PPOS) protocol plus letrozole versus PPOS protocol alone for patients with normal ovarian function who received in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET) assisted pregnancy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…Interestingly, letrozole cotreatment was associated with decreased oocyte maturity and fertilization rates in comparison with standard PPOS protocols even though mature and fertilized oocyte yields were comparable. Previous investigations of letrozole coadministration reported conflicting results on oocyte maturity rate and fertilization rate (Oktay et al, 2006;Quinn et al, 2017;Jiang et al, 2022). Our findings are in accordance with the study published by Quinn et al (Quinn et al, 2017) reporting that letrozole use was associated with a decreased maturity rate compared to the standard GnRH antagonist protocol in breast cancer patients and compared to those undergoing fertility preservation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, letrozole cotreatment was associated with decreased oocyte maturity and fertilization rates in comparison with standard PPOS protocols even though mature and fertilized oocyte yields were comparable. Previous investigations of letrozole coadministration reported conflicting results on oocyte maturity rate and fertilization rate (Oktay et al, 2006;Quinn et al, 2017;Jiang et al, 2022). Our findings are in accordance with the study published by Quinn et al (Quinn et al, 2017) reporting that letrozole use was associated with a decreased maturity rate compared to the standard GnRH antagonist protocol in breast cancer patients and compared to those undergoing fertility preservation.…”
Section: Discussionsupporting
confidence: 86%
“…Currently, letrozole is widely used as an adjunct for IVF cycles (Yang et al, 2021). Cotreatment with letrozole during ovarian stimulation for IVF could significantly reduce gonadotropin consumption in normal and poor ovarian responders without decreasing the number of retrieved oocytes, some even accompanied by increased pregnancy outcomes, while few studies have focused on the clinical characteristics of letrozole coadministration in PCOS patients treated for IVF (Bulow et al, 2022;Jiang et al, 2022). The endocrine and ovulation induction characteristics of PCOS patients are different from those of normal and poor ovarian responders.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the number of oocytes obtained, the number of fertilized oocytes, and the number of available embryos in the Le PPOS group were superior to the traditional PPOS. Previously, Jiang et al 21 reported that Le PPOS could not improve pregnancy outcomes, which was inconsistent with the results of this study. In our study, PSM was used to exclude the difference in outcomes between the two groups caused by the imbalance of factors such as AMH, so it was more reliable.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, oocyte maturity rates were significantly decreased in the LE cotreatment group compared with the PPOS-only group, although mature oocyte yields were comparable. The influence of LE on oocyte maturity remains controversial in the literature (31)(32)(33). LE, an aromatase inhibitor, is usually used in patients who need fertility preservation, such as those with breast cancer, to reduce oestrogen levels (33).…”
Section: Discussionmentioning
confidence: 99%